Voltage-Gated Sodium Channels: Structure, Function, Pharmacology, and Clinical Indications - de Lera Ruiz, Manuel; Kraus, Richard L (Journal of medicinal chemistry, 2015)
The tremendous therapeutic potential of voltage-gated sodium channels (Navs) has been the subject of many studies in the past and is of intense interest today. Nav1.7 channels in particular have received much attention recently because of strong genetic validation of their involvement in nociception. Here we summarize the current status of research in the Nav field and present the most relevant recent developments with respect to the molecular structure, general physiology, and pharmacology of distinct Nav channel subtypes. We discuss Nav channel ligands such as small molecules, toxins isolated from animal venoms, and the recently identified Nav1.7-selective antibody. Furthermore, we review eight characterized ligand binding sites on the Nav channel α subunit. Finally, we examine possible therapeutic applications of Nav ligands and provide an update on current clinical studies.